La curiosidad del jurista persa: método y metodología para una enseñanza emancipadora del derecho constitucional (Tema Central) - Storini, Claudia (2015)
Teaching and researching have found their conceptual unity in the Roman god Jano, whose faces look for the past that condition what we are-our present, and look for the future and possess a special relationship with the independent thinking that researching shows and the teaching transmit. This shows that the fundaments of a teaching role, conducted to an emancipatory education that can be applied from two premises which came from the object of what is thought and its method, has to be elucidated. The study of these two elements will show that the object must be always the same, even if there are various approaches-the reality as a problem; and teaching method, and before researching, only can be one-the critical reason.